Synergistic effects of fluorination on CO2 capture and activation in 1,2,3-triazolium ionic liquids - Gustavo Chacón-Rosales; Cristián Valdebenito; Karina Muñoz-Becerra; Carlos Cruz; Cesar Morales-Verdejo; Kerry Wrighton-Araneda; Pedro Aguirre; Gabriel Abarca (Journal of CO2 Utilization)
The capture and activation of CO₂ remain a pivotal challenge in addressing climate change, requiring innovative materials with exceptional performance. Ionic liquids (ILs) have emerged as highly promising candidates for CO₂ capture due to their tuneable physicochemical properties, negligible vapor pressure, and ability to be tailored for specific molecular interactions with CO₂. Selective fluorination of ILs can enhance key properties, such as thermal stability and CO₂ capture capacity, without necessarily compromising material stability and minimizing potential environmental and toxicological impacts. In this study, we explored the synergistic effects of fluorination in 1,2,3-triazolium-based ILs on CO₂ capture and activation. Two triazole precursors, 1-benzyl-4-phenyl-1H-1,2,3-triazole (TR1) and 1-{[3,5-bis(trifluoromethyl)phenyl]methyl}-4-phenyl-1H-1,2,3-triazole (TR2), were synthesized and used to prepare the corresponding ionic liquids: 1-benzyl-3-(perfluorobutyl)-4-phenyl-1 H-1,2,3-triazol-3-ium iodide (IL-TR1) and 1-(3,5-bis(trifluoromethyl)benzyl)-3-(perfluorobutyl)-4-phenyl-1 H-1,2,3-triazol-3-ium iodide (IL-TR2). Comprehensive structural and electronic analyses, along with CO₂ sorption measurements, revealed that the CO2 up taking of TR1,2-CO2 and IL-TR1,2-CO2 adducts proved to be more favorable in the IL form, enhancing up to 56 % the CO2 adsorption. This enhancement suggests a stronger interaction in IL-TR1,2-CO2 owing to electronic effects compensated by relative energy cost due to structural deformations. This remarkable enhancement is attributed to the synergistic electronic effects introduced by the fluoroalkyl groups, which improve the interaction between the IL and CO₂ molecules. These findings highlight the transformative potential of incorporating fluoroalkyl groups to modulate the performance of triazolium ILs. This work paves the way for the rational design of next-generation fluorinated ILs, offering a promising platform for scalable and efficient CO₂ capture applications.